2023
DOI: 10.1007/s11301-023-00339-3
|View full text |Cite
|
Sign up to set email alerts
|

Music in business and management studies: a systematic literature review and research agenda

Abstract: Music is the background of life, representing an international language that connects different cultures. It is also significant with respect to economies, markets, and businesses. The literature in the music field has identified several issues related to the role of digitalization in the revolution of music, the distribution of music products, the management and organization of music events, music marketing strategies, and the position of musicians as entrepreneurs. This paper comprises a systematic literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…This can be attributed to its direct engagement with the emotional and sensory responses of the audience. Entertainment at music events typically involves a blend of live performances, interactive elements, and perhaps digital enhancements that collectively produce a rich, engaging atmosphere (Pizzolitto, 2023). This aspect of the experience is not merely about passive observation but involves active participation and emotional investment from the audience, which intensifies their overall event satisfaction (Komarac & Ozretić Došen, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be attributed to its direct engagement with the emotional and sensory responses of the audience. Entertainment at music events typically involves a blend of live performances, interactive elements, and perhaps digital enhancements that collectively produce a rich, engaging atmosphere (Pizzolitto, 2023). This aspect of the experience is not merely about passive observation but involves active participation and emotional investment from the audience, which intensifies their overall event satisfaction (Komarac & Ozretić Došen, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, this study acknowledges a fundamental limitation in its analysis due to the diverse nature of concerts in Indonesia, which vary widely not only by musical genre (e.g., K-pop, EDM, indie, and rock) but also by the type of event (e.g., concert, festival, recital, private events, etc.). These variations introduce complexities in uniformly assessing and comparing experiences, potentially affecting the generalizability of the research findings across different types of events (Pizzolitto, 2023). Thus, future research should aim to specifically address the diversity of concert types by developing a more segmented approach in the study of music concert experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Organisational culture includes an organisation's expectations, experiences, and philosophy, as well as the values that guide members' behaviour, and is expressed in member self-image, inner workings, interactions with the outside world, and future expectations. Pizzolitto (2023) observed that the music business needs an innovative culture that promotes the creation of content that captures the imagination of audiences and endorses the use of diverse channels for distributing and selling music. Omidi et al (2020) also stressed that entrepreneurs in the music industry should create a unique social world for consumers through innovative strategies.…”
Section: Introductionmentioning
confidence: 99%
“…This proposition further reinforces the need for an innovative organisational culture in music businesses. Pizzolitto (2023) opines that music artists ought to view themselves as professionals and acquire a livelihood through their musical talent. Therefore, apart from creating good music, they need to develop an innovative market-focused culture that enables them to penetrate markets and distribute their content.…”
Section: Introductionmentioning
confidence: 99%